PENERAPAN MODEL PEMBELAJARAN ROUND TABLE DALAM MENULIS TEKS BIOGRAFI PADA PESERTA DIDIK KELAS X SMK NU SUKAGUMIWANG - Evi Nurmala Sari; Khoirul Fajri; Ade Hasanudin (STKIP Subang, 2025)
The round table learning model was chosen because it can help improve student learning outcomes. This model encourages students to actively participate in group discussions, share ideas, and learn from each other. There needs to be a change, so that students' ability to learn to write biographical texts can improve. Both in terms of emulating, taking inspiration, and understanding the material of the biographical text provided. The purpose of this study is to find out how effective and to describe learning activities using a round table learning model. This study uses a learning outcome achievement test that is prepared in a planned manner to reveal the information of the subject that has been taught. Furthermore, the observation is intended to collect data on the state of the research subject which includes the activities of teachers and students. In this study, the researcher used a quantitative research method using statistics. This research is a type of quasi experiment. The design used is a nonequivalent control group design. The population in this study is all students of class X of SMK NU Sukagumiwang which totals 60 students. The samples in this study are class X TKJ and class X TKRO. The sample technique used is saturated samples. The results showed that the average final learning outcome of the experimental class was 76.6 while the average final score of the learning outcome of the control class using the direct learning model was 73.6. The results of the research test can be seen at the value of Sig. (2-tailed) of 0.047 < 0.05, then it is known that the tcount value is 22.033 > t table 2.002. Based on the above, it was rejected and accepted, which means that the application of the round table learning model in writing the biography text of class X students of SMK NU Sukagumiwang is effective.